Psychological occupational stress: Dangers of the hospital environment as a model - Ait-Aldjet, Megdouda (Art Law and Accounting Reporter, 2025)
Hospital personnel are the most highly vulnerable to occupational stress. Their daily presence during work especially in emergency units (almost intensive care and serious illnesses) exposed them to extreme situations as the inability to adapt, poor performance, incapacity to achieve daily tasks, lack of motivation to work, and psychological fatigue. Several reached studies have confirmed that medical staff are among exposed professionals to occupational stress. Multiple studies have identified several causes of this occupational stress with the most significant of them being: heavy workload and multi-tasks, social pressures with management, colleagues, and companions of patients, low social support, low rewards, and wages, not to mention that they are also exposed to day-to-day of patients suffering, pain, and death . Offering all these issues and other stress factors that medical staff are exposed to, they have an even more significant problem to solve in their day-to-day lives: exposure and subsequent infection with infectious diseases that may either be chronic or fatal.
Keywords: medical staff; psychological occupational stress; hospital environment risks